Coming Together: A Case Study of Collaboration Between Student Affairs and Faculty at Norfolk State University - Commodore, Felecia; Gasman, Marybeth; Conrad, Clifton; Nguyen, Thai-Huy (Frontiers in Education, 2018)
This article takes a look at an HBCU whose initiatives are contributing to rising freshmen retention rates. We give particular focus to the role of collaboration between academic and student affairs to facilitate this success. In analyzing interviews from key constituents surrounding retention initiatives, the role and relationship of the collaboration of academic and student affairs with student retention will be discussed. Motivations and strategies for collaboration in the unique HBCU context are explored. Through this paper, the reader learns more about the way in which coordination and collaboration—between academic and student affairs—aids in fostering student success, particularly in an under resourced environment.